1999
DOI: 10.1128/jvi.73.4.2752-2761.1999
|View full text |Cite
|
Sign up to set email alerts
|

Identification of CXCR4 Domains That Support Coreceptor and Chemokine Receptor Functions

Abstract: The interaction of the chemokine stromal cell-derived factor 1 (SDF-1) with its receptor CXCR4 is vital for cell trafficking during development, is capable of inhibiting human immunodeficiency virus type 1 (HIV-1) utilization of CXCR4 as a coreceptor, and has been implicated in delaying disease progression to AIDS in vivo. Because of the importance of this chemokine-chemokine receptor pair to both development and disease, we investigated the molecular basis of the interaction between CXCR4 and its ligands SDF-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
72
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(75 citation statements)
references
References 66 publications
3
72
0
Order By: Relevance
“…Such diversity among HIV strains in their structural requirements for functional interaction with CXCR4 was previously reported by Brelot et al [29,31]. Also, Doranz et al found that amino acid residues in all four extracellular regions of CXCR4 contribute to coreceptor activity, implying that the viral envelope interacts with a conformationally complex structure of the receptor protein [32]. Yet, AMD3100 is potently and consistently active in the nanomolar range against every CXCR4using HIV-1 strain tested so far, including those viruses that for their infectivity do not depend on the presence of aspartic acid residues at positions 171 and/or 262 of the coreceptor (e.g.…”
Section: Coreceptor E⁄ciency Of the Cxcr4 Mutants For Diversementioning
confidence: 60%
“…Such diversity among HIV strains in their structural requirements for functional interaction with CXCR4 was previously reported by Brelot et al [29,31]. Also, Doranz et al found that amino acid residues in all four extracellular regions of CXCR4 contribute to coreceptor activity, implying that the viral envelope interacts with a conformationally complex structure of the receptor protein [32]. Yet, AMD3100 is potently and consistently active in the nanomolar range against every CXCR4using HIV-1 strain tested so far, including those viruses that for their infectivity do not depend on the presence of aspartic acid residues at positions 171 and/or 262 of the coreceptor (e.g.…”
Section: Coreceptor E⁄ciency Of the Cxcr4 Mutants For Diversementioning
confidence: 60%
“…The ®rst 17 AA, which are identical in all isoforms, are required for the binding of the SDF-1 proteins to CXCR4 (Loetscher et al, 1998;Doranz et al, 1999). At the other end, in the carboxy-terminal region of SDF-1b, a pair of basic AA (lys 89, arg 90) provides a motif for proteolytic cleavage by a membrane-bound protease of the trans-Golgi apparatus and secretory vesicles, that would result in a pentapeptide (lys 89 ± met 93) and a shortened core protein.…”
Section: Discussionmentioning
confidence: 99%
“…1) raises the possibility that the remaining 19 residues are, either directly or indirectly, involved in specifically recognizing SDF-1 and/ or mediating CXCR4 activation by SDF-1. Functional analysis of hCXCR4/hCXCR2-chimera and hCXCR4 mutants showed that the amino-terminal-most portion of hCXCR4 up to the residue corresponding to Pro 31 of xCXCR4 is important for high-affinity SDF-1 binding, but is neither necessary nor sufficient for receptor activation by high concentrations of SDF-1 [37]. Results obtained very recently by NMR solution structure analysis of a complex between the CXC chemokine IL-8 and an amino-terminal hCXCR1 peptide revealed that nine amino-terminal residues of hCXCR1, corresponding to Gly 23 -Pro 31 of xCXCR4 are likely to directly interact with, and thus constitute part of, the receptor recognition site for IL-8 [38].…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, four of these residues, Gly 23 , Asp 24 , Glu 30 , and Pro 31 of xCXCR4, are absolutely conserved between X. laevis and mammalian CXCR4, suggesting an important role of these residues in the binding of SDF-1 to CXCR4. On the other hand, residues present within the second and the third extracellular loop appear to be important for SDF-1-mediated activation of CXCR4 [37]. For example, replacement of the Glu 179 -Ala-Asp-Asp motif present within the second extracellular loop of hCXCR4 by Gln-Ala-Ala-Asn blocked activation of CXCR4 by SDF-1.…”
Section: Discussionmentioning
confidence: 99%